Personalized nutrigenomics: tailoring the diet to the aging diabesity population - Douglas M Ruden; Xiangyi Lu (Nutrition and Dietary Supplements, 2011)
Douglas M Ruden1, Xiangyi Lu21Wayne State University, Department of Obstetrics and Gynecology, C. S. Mott Center for Human Growth and Development, Institute of Environmental Health Sciences, Detroit, MI, USA; 2Institute of Environmental Health Sciences, Eugene Applebaum College of Pharmacy and Health Sciences, Detroit, MI, USAAbstract: According to the International Diabetes Federation (IDF), 190 million people worldwide suffer from diabetes, and this number is estimated to double by the year 2025. Diabetes is especially prominent in the elderly population because the IDF indicates age above 45 years as a major risk factor for diabetes. The most common trials for controlling diabetes focus on tighter glucose control as a means to reduce the long-term complications. However, whether tight blood sugar control or other dietary or pharmaceutical interventions in the elderly are more appropriate is not known. Major changes have taken place in our diet over the past 10,000 years since the beginning of the Agricultural Revolution, but our genes have not changed. Furthermore, the large numbers of diabetic elderly in the population are a recent phenomenon, because those with diabetes have historically died young. Genetically speaking, humans today live in a nutritional environment that differs from that for which our genetic constitution was selected. For example a high omega-6/omega-3 ratio, found in today’s Western diets, promotes the pathogenesis of many chronic diseases, including cardiovascular disease and diabetes. Knowing who is at risk would be useful if it meant that one could avoid the environmental triggers that convert susceptibility to disease. The prospect of targeting specific dietary treatments at the elderly, who are predicted to gain the most therapeutic benefits, clearly has important clinical and economic consequences. In this review, we will discuss modern molecular genetic and epidemiological techniques which are now, or soon will be, made available by inexpensive whole-genome sequencing and other whole genome approaches to treat the elderly diabetic population.Keywords: diabetes, elderly diabetic population, DNA, genome sequencing